Workshop | Co-designing interventions to increase demand for fruit & vegetables in Tanzania - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
How can we make fruit and vegetables more desirable to communities in Tanzania? In August 2024, the CGIAR Research Initiative on Fruit and Vegetables for Sustainable Healthy Diets (FRESH) teamed up with IFPRI and the Global Alliance for Improved Nutrition (GAIN) to facilitate a stakeholder workshop focused on co-designing demand-side interventions.